Using The Multiliteracies Approach To Promote Learner Engagement In An Esl Classroom: A Case Study In A Selected School In Penang - Ganapathy, Malini Alp N.G. (2007)
This study is primarily an investigation of using the Learning by Design Framework (LBO F) underlying the Multiliteracies Approach (MLA) to promote learner engagement in an ESL classroom. The study also analyses students' . perceptions of their learning experiences using the MLA to acquire their language skills in the ESL classroom. The study further examines teachers' perceptions of the LBO using the MLA for literacy pedagogy in the ESL classroom to determine the extent of its effect on students' ability in demonstrating the knowledge processes based on the MLA of lessons. The study also aims to produce a set of guidelines that will help teachers design and implement learning experiences based on the teachers' perceptions of the MLA. The conceptual framework that underpins the study includes theoretical studies in second language acquisition and approaches to teaching and learning contexts in ESL classrooms. The sample comprises 33 secondary school students and five ESL teachers in Convent Light Street Secondary School in Penang. The study employs both quantitative and qualitative data collection techniques such as questionnaires, semi-structured interviews and student journals. The sample of 33 Form Four students kept student journals to record their learning experiences based on the MLA lessons (16 weeks). The qualitative data from interviews and student journals were analysed, categorised and sorted into the domains that reflect the perceptions of teachers and students. Respondents' perceptions and opinions of the LBDF underlying the MLA are presented in the findings, which are illustrated through the use of excerpts from interview responses and journal entries. The findings of the study indicate that the LBDF underlying the MLA has crucial implications for improving the quality of teaching and learning in schools. This study shows that students' academic achievement is positively correlated to integration of leT when the teacher addresses their real world needs in the classroom setting by integrating technology as an educational tool which enables the achievement of learning outcomes successfully. This ease study reveals that the MLA to teaching and learning through the knowledge processes in the LBDF ensures that students would be able to understand the knowledge and skills that they acquire through collaborative activities where students felt that they were self-motivated and possessed the desire to explore, discover and critically assess relevant materials.